On certain class of analytic functions based on poisson distribution - Najafzadeh, Shahram (Penerbit Universiti Kebangsaan Malaysia, 2020)
In this paper, a power series whose coefficients are the probabilities of the Poisson distribution is considered. A new subclass of univalent holomorphic functions related to Poisson distribution and convolution is introduced. Some properties such as coefficient estimates, distortion bounds, radii of starlikeness, convexity and close-to-convexity are obtained. The neighbourhood property for functions in this new subclass is also given.